INVESTIGATION OF THE ACTIVITY OF 8- METHYLQUINOLONES AGAINST MYCOBACTERIUM TUBERCULOSIS USING THEORETICAL MOLECULAR DESCRIPTORS: A CASE STUDY - Eric, Gowal M.; Uzairu, Adamu; Mamza, Paul A.P (European Scientific Journal, ESJ, 2015)
A quantitative structure-activity relationship (QSAR) study on a set of 36 structurally-similar 8-methylquinolones was performed using a large pool of theoretical molecular descriptors. The molecular structures of the compounds were pre-optimized using molecular mechanics (MM2). Full optimization was done with the density functional theory (DFT) using Becke’s three-parameter hybrid functional with LYP correlation functional in combination with the standard pople’s basis set 6311G*. HOMO and LUMO energies, dipole moment, total energy and many other properties served as quantum-chemical descriptors. The GA-MLRA technique was used to select the most significant descriptors and to generate a linear model for predicting the biological activity, Minimal Inhibitory Concentration (MIC), treated as negative decade logarithm, (pMIC). The best model was obtained with R2=0.90323 . The model was tested internally using the leave-one-out (LOO) cross validation procedure on the training set and validated against the external validation set (Q2 LOO = 0.83115 and R2 Pred = 0.78708 ). The Y-scrambling/randomization validation also confirmed the statistical significance of the model. Leverage approach was used to define the applicability domain of the model. This validated model could be used to design new potential drug candidates, within the 8-methylquinolone family, with high activity against tuberculosis.